Downlink adaptive array algorithms for cellular mobile communications - Morgan, D.R. (IEEE transactions on communications, 2003)
The capacity of wireless downlink communication to mobile receivers in a dense urban environment is limited primarily by co-channel interference. Downlink adaptive arrays can be used to mitigate this limitation by maximizing the power transmitted to desired in-cell mobiles in the reference cell while minimizing power to co-channel mobiles in neighboring cells. This is accomplished by using uplink measurements to estimate downlink covariance matrices and then solving a generalized eigenvalue problem. Several algorithms are proposed to adaptively estimate the optimal solution and are evaluated using a simplified signal model that allows efficient deterministic performance calculations.